2013
DOI: 10.1088/0957-4484/24/38/384005
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory of TiO2-based electrochemical capacitors: empirical analysis with adoption of a sliding threshold

Abstract: Chemical synapses are important components of the large-scaled neural network in the hippocampus of the mammalian brain, and a change in their weight is thought to be in charge of learning and memory. Thus, the realization of artificial chemical synapses is of crucial importance in achieving artificial neural networks emulating the brain's functionalities to some extent. This kind of research is often referred to as neuromorphic engineering. In this study, we report short-term memory behaviours of electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Further, the BCM model predicts different regimes of LTP and LTD depending on the state of the post-synaptic neuron, while a sliding threshold separates this into two regimes [32]. Recently, Lim et al [33] showed evidence that BCM-like plasticity can be emulated with memristive devices and derived an empirical equation in the framework of a firing-rate-model by introducing a time-depending threshold function. Here, we would like to derive an empirical plasticity model, which itself avoids an unlimited weight growth and where the sliding threshold depends on the current synaptic weight and therewith on the state variable .…”
Section: Plasticity Modelmentioning
confidence: 99%
“…Further, the BCM model predicts different regimes of LTP and LTD depending on the state of the post-synaptic neuron, while a sliding threshold separates this into two regimes [32]. Recently, Lim et al [33] showed evidence that BCM-like plasticity can be emulated with memristive devices and derived an empirical equation in the framework of a firing-rate-model by introducing a time-depending threshold function. Here, we would like to derive an empirical plasticity model, which itself avoids an unlimited weight growth and where the sliding threshold depends on the current synaptic weight and therewith on the state variable .…”
Section: Plasticity Modelmentioning
confidence: 99%
“…Memristors are promising candidates for both neuromorphic computing and next generation nonvolatile memory applications [1][2][3][4][5][6][7] because of their scalability [3,8] , 3D stacking potential [9][10][11] , and a close resemblance to the operating characteristics of synapses [1,4,7,12,13] . These applications typically require a large crossbar array of memristors, in which sneak path currents from neighboring cells during a write or read of a target cell can severely impede the proper operation of the array.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a drastic research paradigm shift toward memristive devices may enable a new approach of full memristive neural networks (FMNN) for achieving bioplausible neural networks with great scaling potential . Significant progress has been made on memristive synapses, which can simulate rich synaptic functionalities on a single nanodevice . Especially, by utilizing the dynamic memory switching effect, memristors has been proposed to simulate the synaptic learning rules, leading to a more biological artificial synapse.…”
Section: Introductionmentioning
confidence: 99%